Cultivation Theory - Saefudin, Asep; Venus, Antar (FIkom Unisba, 2007)
The idea of Cultivation Theory was first addressed by George Gerbner with his colleagues of Annenberg School of Communication, Pennsylvania (1969). Based on previous research about cultural indicators conducted by the same researcher, cultivation analysis focused on mass media impact on everyday life. Another important findings from cultivation analysis was the categorization of television audience to two different classes: heavy viewers and light viewers. Among those two, heavy viewer became the main concern of communication scholars. It was believed that heavy viewing of television behavior permanently would lead to deep and exaggerated belief toward symbolic realities as presented on the screen.